Fotografia, educação e cultura : diálogos com os fenômenos - Capai, Humberto Derci (2013)
It reveals photography combined with other areas of knowledge particularly sociology, philosophy and psychology within an educational know-how and knowin- the-make, as well as the relationship of photography to graphic design in research, culture and art by producing books with photos and texts (photobooks). It highlights photography as a strong element for an educational and cultural interaction as well as a language of representation of the world. It encourages the use of photography and its editing in books related to education and to culture and it presents works based on photography that articulate photography, science and education. It also stimulates the production of photographs for teaching and education, considering the cultural reference of the student and the teacher. It exemplifies and pays reverence to a method of research and educational work built in the perspective of a better and happier life, the essential aim of science, culture and education. It presents results, questions and notes from three decades dedicated to teaching, education and culture, a path that had photography as a permanent companion in its various conceptions: art, language, technique and artifact. It reveals a practice of educating able to transform itself and to continuously generate changes from the interaction with the educational phenomenon essentially human itself , in which are present the actors involved and the knowledge developed by mankind. It raises the possibility of producing scientific and educational work in languages and formats practiced by the population, which may be useful to teachers and students of many different levels in order to bring contributions to their lives and to develop the topics covered here. Likewise, it addresses all those who believe that as we educate, we educate ourselves.